SYNTHESIS AND CHARACTERIZATION OF HEMATITE (Fe2O3) OF IRON ORE AND MAGNETITE (Fe3O4) FROM IRON SAND THROUGH PRECIPITATION METHOD FOR INDUSTRIAL RAW MATERIALS - Fatmaliana, Andia; Maulinda, Maulinda; Sari, Nirmala (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
Indonesia is a country that has enormous iron ore and iron sand mine that can be utilized for various industrial purposes. This research has been successfully conducted synthesis and characterization of hematite iron ore and magnetite from iron sand. Iron sand and iron ore that has been crushed manually repaired with a magnet was carried out with the HCl, and NH4OH then dried in the temperature of 150 oC and calcinated at a temperature of 500 oC. Characterization was carried out using X-ray diffraction (XRD) and X-ray fluorescence (XRF), where the preliminary information obtained from XRF results in an iron ore sample by manual separation have 95.99% of Fe2O3 and followed by compounds SiO2 (2.10%). While the iron sand contains 81.42% of Fe3O4 and 2.5% of SiO2. After the precipitation process, Fe2O3 compounds contained in iron ore has a content of 96.58% and Fe3O4 compounds contained in iron sand (86.73%). Â The results of XRD indicate the dominant primary phase in iron ore is hematite or Fe2O3, and in iron, sand is magnetite Fe3O4, Before the extraction process, Fe2O3 was 58.009 Î¼m in size and after the process of extracting the particles was reduced to 20.950 Î¼m. While the Fe3O4, prior to the extract, has a grain size of 59.009 Î¼m, and after an extraction process, the grain size reduced into 25.950 Î¼m. The calculation results indicate there is a slight size difference between the grain size of iron sand and iron ore.